The origin and collapse of rock glaciers during the Bølling-Allerød interstadial: a new study case from the Cantabrian Mountains (Spain) - Santos-González, Javier (2022)
During the Late Pleistocene, the main mountain ranges of the Iberian Peninsula were covered by small icefields and cirque and alpine glaciers. The deglaciation triggered paraglacial processes that generated landforms, mostly within the ice-free glacial cirques. In this research we analyse the deglaciation process in the Muxivén Cirque (42°15′N – 6°16′W), in the upper Sil River Basin, which includes some of the largest relict rock glaciers of the Cantabrian Mountains. We addressed this objective by means of accurate geomorphological reconstructions, sedimentological analysis, Schmidt-hammer surface weathering measurements and a dataset of 10 10Be Cosmic-Ray Exposure ages. Results reveal that after ~16 ka, glaciers retreated to the bottom of the cirques at the headwaters of the valley, leaving the walls free of ice and triggering rock avalanches onto the remnants of these glaciers. This paraglacial process supplied debris to a small glacier within Muxivén Cirque, which transformed in two rock glaciers. These debris isolated the ice inside the rock glaciers only for a very short period of time and ended up melting completely before the Younger Dryas. The lower sector of the largest one stabilized at 14.5 ± 1.5 ka, while the upper sector remained active until 13.5 ± 0.8 ka. Previous to the stabilization of the lower sector of the northern rock glacier, at its margin a high-energy debris avalanche occurred at ~14.0 ± 0.9 ka. These data agree with previous research, corroborating the paraglacial origin of most Iberian rock glaciers during the Bølling-Allerød interstadial.